2021
DOI: 10.3390/agronomy11030471
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Elimination of the Allelochemical MBOA by Weeds during Seedling Growth

Abstract: 6-Methoxy-2-benzoxazolinone (MBOA) is an allelochemical that is found in Poaceae and is generally associated with monocotyledon species. This compound is formed from the glycosylated form of 2,4-dihydroxy-(2H)-1,4-benzoxazin-3(4H)-one (Gly-DIMBOA) by a two-stage degradation process. The MBOA detoxification capacity of two weed species, namely Echinochloa crus-galli and Lolium rigidum, and a resistant biotype of Lolium rigidum (SLR31) was studied both qualitatively and quantitatively. The product of metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The aim was to quantify the Hx content in both plant tissues and the transmission medium. This approach was informed by prior studies on Hx transportation and absorption, 22 and we hoped to construct a comprehensive picture of the Hx transportation route.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim was to quantify the Hx content in both plant tissues and the transmission medium. This approach was informed by prior studies on Hx transportation and absorption, 22 and we hoped to construct a comprehensive picture of the Hx transportation route.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, while wheat is able to influence weeds by secreting DIMBOA, 21 studies have shown that weeds can transmit the previously absorbed compounds to the medium by root exudation. 22 The investigation of interplant chemical recognition and response characterized by alterations in secondary metabolites holds great significance in expanding our understanding of chemical interactions among plant species. Therefore, for a more comprehensive understanding of the allelopathic disturbance mechanism, it is necessary to study the transformation and transport of secondary metabolites between wheat and neighboring plants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation